A Cost-Effectiveness Evaluation of Hospitalizations, Fatalities, and Economic Outcomes Associated with Universal Versus Anaphylaxis Risk-Stratified COVID-19 Vaccination Strategies - Shaker, Marcus (J Allergy Clin Immunol Pract, 2021)
BACKGROUND: Vaccine-associated anaphylaxis is a rare event (1.34 events/million doses; 0.00017% occurrence over 26 years). Several reports of allergic reactions concerning for anaphylaxis have been reported early into the Pfizer-BioNTech and Moderna coronavirus disease 2019 (COVID-19) vaccine campaign in the United States, Canada, and the United Kingdom. OBJECTIVE: To perform a cost-effectiveness analysis characterizing the risks of COVID-19 versus vaccine anaphylaxis, comparing universal COVID-19 vaccination versus risk-stratified vaccination approaches. METHODS: Cohort analysis models were created to evaluate the cost-effectiveness of universal vaccination versus risk-stratified vaccination (eg, contraindicated in persons with a history of any previous episode of anaphylaxis) with a threshold for cost-effective care at $10,000,000 per death prevented. In the base case, risk of anaphylaxis was estimated at 0.1%, with case-fatality estimated at 0.3%. RESULTS: On a population level (n = 300,000,000 simulated persons), universal vaccination was associated with a cost-savings of $503,596,316 and saved 7,607 lives, but the cost-savings was sensitive to increasing rates of vaccine-associated anaphylaxis. The universal strategy dominated at higher rates of COVID-19 infection and low rates of vaccine-associated anaphylaxis in both the health care and societal perspectives. When the risk of vaccine-associated anaphylaxis exceeded 0.8%, the risk-stratified approach to vaccination was the most cost-effective strategy. There was also an interaction between anaphylaxis risk and anaphylaxis fatality, with a risk-stratified approach becoming cost-effective as each risk increased concurrently. Stratified observation time by anaphylaxis history (15 minutes vs 30 minutes) was not cost-effective until a 1% anaphylaxis case-fatality was assumed and risk of vaccine anaphylaxis exceeded 6%. CONCLUSIONS: This study demonstrates that unless vaccine anaphylaxis rates exceed 0.8%, a universal vaccination approach dominates a risk-stratified approach where persons with any history of anaphylaxis would be contraindicated from vaccination, with lower cost and superior health outcomes.